Experimental study of biofilm-forming ability to methicillin-resistant and methicillin-susceptible Staphylococcus strains - Voronkina, I; Derkach, S; Krilova, I; Gabysheva, L (Annals of Mechnikov’s Institute, 2020)
In medicine there are many methods for studying of formation of biofilms. Cultivation in dynamic systems allows to create the conditions as much as possible close to that exist in the macroorganism. The majority of experimental methods are based on building of static culture conditions of microorganisms, most often for this purpose use 96-well plastic microplates in various modifications.Using microplates even one manufacturer leads to different results of the study, which is due to physical and chemical characteristics. In addition, the formation of biofilms using this method affects the composition of culture media (micronutrient and electrolyte) and aeration degree.To quantify biofilm formation in microplates researchers use the various wavelengths of the photometer: 450 nm, 540 nm, 562 nm, 630 nm, 650 nm, etc.Thus, this method is quite common, but its basic lack is that there are no standards that would allow it to unify all laboratories.The aim of this study was to optimize the test parameters to detect the ability of film formation MRSA and MSSA strains.Materials and methods. We used staphylococcus strains: S.aureus ATCC 25923, strains from the laboratory of the museum with a certain in previous studies of methicillin-sensitive and recently received S.aureus strains from patients with purulent-inflammatory diseases of different localization. Defining the properties of a biofilm forming staphylococcus culture plates was performed by D. Christensen.Results and discussion. In this experiment nutrient broth (HiMedia, India) was used with different volume fractions ingredients: 2 % glucose, 6 and 7 % NaCl.Microplates were incubated 4, 24, 48 and 72 hours at 35 ˚C.Optical density of formed biofilm evaluated by the color intensity of spirit on a photometer (StatFax 303 Plus).This method was studied biofilm-forming properties of staphylococcus obtained from all 36 patients with community-acquired methicillin-resistant (MRSA) (n = 16) and methicillin-susceptible (MSSA) (n = 20) strains.It is defined that from 16 strains MRSA of 12,5 % had high ability to biofilms formation of (OD 0,25-0,4 units), 3 strains of 18,75 % - an average (OD 0,12-0, 24 units), - have found 43,75 % weak ability to formation of biofilms (OD <0,12 units), 25,0 % - a biofilm did not create in general (an authentic difference in comparison with the control well it is not revealed).It was defined that among 16 strains of MRSA 12.5 % had a high ability to form biofilms (OD 0,25-0,4 units.), 18.75 % - average (OD 0,12-0, 24 units), 43.75 % - found weak ability to form biofilms (OD <0.12 units.) and 25.0% - do not create biofilm (significant difference compared with control wells not detected).MSSA strains also differ in their ability to form biofilms. 30.0 % of the isolates were referred to the fact that not form a biofilm, 40.0 % - to strains with weak ability to form a biofilm, 20.0 % - with the average, 10.0 % are highly active biofilm formation. Conclusions. 1. The optimal parameters for the experimental determination of the ability of biofilm formation of staphylococcus strains are: use of nutrient broth with the bulk part of the 2 % glucose, incubating the plates for 24-48 hours at 35 °C. The measurement of the optical density (OD) of the resulting biofilms should be performed at wavelength of 630nm. 2. Experimental confirmation of a high ability to form biofilm in the studied strains of staphylococci occurred in 10.0 % MSSA and 12.5 % - MRSA. 25.0 - 30.0 % of the strains were classified as not forming a biofilm, and the rest - to the cultures with weak or medium activity. 3. As a result of a comparative study of the ability to form biofilms of circulating strains of community-acquired staphylococcus significant difference between MRSA with methicillin-resistant phenotype and MSSA strains not detected (χ2> 0.05).